Minimally painful retrieval of ureteral stent by using ureteroscopy - Kadir Önem (Journal of Clinical and Experimental Investigations, 2010)
Aim: The standard method for retrieving the ureteral stents is the cystoscopic technique. We describe a minimally painful method for retrieving ureteral stents by using an ureteroscope.Methods: A total of 60 patients with ureteral stents were enrolled in this study. The patients were randomized into a cystoscopic (30 cases) and an ureteroscopic (30 cases) group. All stents were retrieved by a cystoscope in the first group and by an ureteroscope in the second group, under topical anesthesia. Patients in each group were assessed for stented time, stent side and reason of stent placement, operative time, peroperative pain, postoperative pain, irritative voiding symptoms and hematuria.Results: Stents were successfully retrieved in 60 patients. There were no statistical differences in the two groups regarding patient’s gender and age or stent side, operative time and stented time (p>0.05). Mean operative pain score was significantly higher in the cystoscopic group than in the ureteroscopic group (p<0.01). The irritative voiding symptom scores and hematuria were more prevalent in the first group than the second (p< 0.05).Conclusion: In present study ureteroscopic stent retrieval was found to be minimally a painful, safe and reliable method. The ureteroscopic retrieval procedure is highly tolerable by patients than the cystoscopic retrieval. We suggest that it may be the standard technique for stent retrieval. J Clin Exp Invest 2010; 1(1): 7-11